Lazar Brankov and the Yugoslav communist emigrants in Hungary (1948-49) - Vukman, Péter (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2014)
Communities of so-called Informbureau (ibeovci) emigrants were established in the Soviet Union and its Eastern European satellites after 1948 as part of the Soviet-Yugoslav conflict. In Hungary, it was Lazar Brankov who first took an active role in organizing the emigrant community and led their political activities. The scope of this article covers the short period between October 1948 and June 1949, during which Brankov was the leader of the ibeovci emigrants in Hungary. A careful analysis of the archival sources suggests, rather, that he emigrated of his free will and with the knowledge of the Hungarian and Soviet party leadership. He immediately took an active part in the political activities of the emigrants. At the turn of 1948-49, the emigrants formed only a small community in Hungary. Their everyday lives were based on collectivist morals and supervised by the agents of the Hungarian secret police. Brankov´s arrest in June 1949 had a dramatic and destructive effect on the emigrants´ lives.
Keywords: Brankov, Lazar, 1912-2011; Sovjetska zveza; Yugoslavia; Jugoslavija; mednarodni konflikti; Informbiro; Informbiro period; emigracija; politični emigranti; madžarsko-jugoslovanski odnosi; 1948-1949; politična zgodovina